The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pgen.1004411
|View full text |Cite
|
Sign up to set email alerts
|

Sgo1 Regulates Both Condensin and Ipl1/Aurora B to Promote Chromosome Biorientation

Abstract: Correct chromosome segregation is essential in order to prevent aneuploidy. To segregate sister chromatids equally to daughter cells, the sisters must attach to microtubules emanating from opposite spindle poles. This so-called biorientation manifests itself by increased tension and conformational changes across kinetochores and pericentric chromatin. Tensionless attachments are dissolved by the activity of the conserved mitotic kinase Aurora B/Ipl1, thereby promoting the formation of correctly attached chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
119
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(133 citation statements)
references
References 52 publications
13
119
1
Order By: Relevance
“…Thus, we first examined the sensitivity of rts1D mutants to CIK1-CC overexpression. rts1D cells harboring P GAL CIK1-CC plasmids grew very poorly on galactose plates ( Figure 4A), which is consistent with a previous observation (Peplowska et al 2014). Moreover, after 6-hr incubation in galactose medium, 62% of rts1D cells with P GAL CIK1-CC plasmids were inviable, whereas only 8% of rts1D cells with a vector lost viability.…”
Section: Rts1 Prevents Sac Silencing In the Presence Of Syntelic Attasupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, we first examined the sensitivity of rts1D mutants to CIK1-CC overexpression. rts1D cells harboring P GAL CIK1-CC plasmids grew very poorly on galactose plates ( Figure 4A), which is consistent with a previous observation (Peplowska et al 2014). Moreover, after 6-hr incubation in galactose medium, 62% of rts1D cells with P GAL CIK1-CC plasmids were inviable, whereas only 8% of rts1D cells with a vector lost viability.…”
Section: Rts1 Prevents Sac Silencing In the Presence Of Syntelic Attasupporting
confidence: 90%
“…However, the observation that the tension sensing by Ipl1 is independent of the centromere localization of Ipl1 complex argues against this possibility (Campbell and Desai 2013). Consistently, overexpression of the Ipl1 cofactor SLI15 restores centromere Ipl1 localization in sgo1D mutants, but this fails to suppress sgo1D's sensitivity to CIK1-CC overexpression (Peplowska et al 2014). Here, we further showed that sgo1D mutation alleviated the anaphase entry delay in the phospho-mimetic mutant dam1-3D.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations